DURATION OF POSTVACCINAL IMMUNITY AGAINST HEPATITIS B IN HEALTH CARE WORKERS IN ST. PETERSBURG - Z. P. Kalinina (Sankt-Peterburg : NIIÈM imeni Pastera, 2015)
Immunization against hepatitis В is the most effective method of preventing this disease. Study of quantitative characteristics of postvaccinal immunity against viral hepatitis В in 214 health care workers from different institutions of St. Petersburg has shown that HBV vaccine provides a long term immunity in 80% of cases with the absence of manifest forms of the disease. The duration of circulation of high titers of antibodies depended on the age of people when vaccination was provided. The highest level of immunity was observed in people vaccinated before the age of 30 years (84,0–90,6%). Reduction of immunity level in vaccinated health care workers after 5 years from the date of vaccination requires revaccination against viral hepatitis B after pre-vaccination screening.